Dos salões de ginástica ao Instagram: comunicação e valores de consumo nas narrativas publicitárias - Cardoso, Raissa Gomes Freire (2021)
In a context in which brands try to adapt to the changes happening in the world in order to survive market competition, we understand the need to research about communication and consumption in pandemic times that the population is living. The present work sought to understand the communicational strategies used by three brands in the fitness center segment in the city of São Paulo. Therefore, we conducted an exploratory research in the Instagram profile of each company, being divided into three periods (before the emergence of Covid-19, during social isolation and after the return of face-to-face activities with restrictions), aiming to compare the advertising narratives and the consumption values present in each stage of analysis to reflect on possible transformations and content sharing. Thus, we understand the need to resume points about the meaning of consumption in different times and the history of advertising in Brazil, until arriving at the corpus of the research, in addition to the role of aesthetics, as a fundamental tool of communication.